Da epistemologia metafísico-teológica medieval à teoria de sistemas sociais autopoiéticos - Guerra Filho, Willis Santiago (2013)
The essay brings a historic building that covers the metaphysical epistemology used by the Christian theology and disembarking in the theory of systems, featuring some thinkers of their epochs, defending a philosophical stance that embraces the current moment that one experiences.